(untitled) (Czech Journal of International Relations, 1995)
Kari Dietrich Bracher, Manfred Funke, Hans-Adolf Jacobsen (eds.): Germany, 1933-1945. Studies on History and Politics. Series of Publications. Volume 314. Federal Agency for Civic Education, Bonn 1993, 632 pages, ISBN 3-89331-185-8.